Effect of biochar-amended soil substrates on the growth of chinese kale in an organic system - Dechjiraratthanasiri, Chatprawee; Khuansri, Kotchapan; Wongsiriamnuay, Thanasit; Inthasan, Jiraporn (Health Science, Science and Technology Reviews, 2025)
Study of the effects of biochar-based growing media on the growth of kale. This study aimed to utilize agricultural waste for biochar production as an alternative to open burning, which is harmful to the environment. The experiment was designed using a completely randomized design (CRD) with 5 replications and 11 treatments. These treatments consisted of biochar produced from various types of agricultural waste, including 1) rice straw, 2) rice husk, 3) longan leaf, 4) longan peel, 5) longan branch, 6) jarul branch, 7) mango leaf, 8) corncob, 9) coffee husk, and 10) tobacco stem, which were mixed with commercially available growing media and cow manure in a ratio of 2:1:1 (growing media: biochar: cow manure).The study investigated the effects of different biochar types on the growth of chinese kale (Brassica alboglabra) in organic growing media. The results demonstrated significant improvements in growth parameters, including plant height, fresh and dry weight from substrate mixed with tobacco stems whereas the highest chlorophyll content was found in culture mixed with mango leaf biochar. The incorporation of biochar into the soil culture boosted its chemical and biological properties. Biochars derived from jarul branches, tobacco stems, and corncobs led to higher pH, electrical conductivity, organic carbon content, and amounts of water-soluble phosphorus and potassium compared to the control. Additionally, coffee husk biochar recorded the highest microbial population, reaching 10.7 × 105 CFU g-1soil at harvest time. These findings highlight the potential of various biochar as effective amendments for improving soil fertility and promoting plant growth in organic farming systems.